Inovasi Strategi Pembelajaran Dalam Meningkatkan Efektivitas Pendidikan Abad 21: Sebuah Studi Literatur - Titi Anita (Jurnal Sultra Elementary School, 2024)
21st-century education presents significant challenges that require innovation in teaching strategies. Technological advancements, social developments, and the demand for 21st-century skills influence how education is implemented worldwide. This literature review aims to explore various innovations in teaching strategies that can enhance the effectiveness of 21st-century education. Innovations discussed include project-based learning, the utilization of information and communication technology (ICT), and differentiated instruction that can accommodate the diverse needs of students. Based on the literature review, these innovations have been proven to encourage students to become more active, creative, and critical in the learning process, as well as help them develop skills relevant for the future.